The Crime Of Assault On Non-Islamic Sacred Sites From The Perspective Of Islamic Jurisprudence And Its Impact On The Economy And Sustainable Development - El-Sayed Abu El-Ala, Khaled Fouad (Journal of Neonatal Surgery, 2025)
The research aimed to define the crime of assault on non-Islamic sacred sites, its ruling from the perspective of Islamic jurisprudence, its penalty, and to clarify the effects thereof from both the Sharia and legal perspectives. The study relied on the descriptive method, and within that framework adopted the analytical approach. It resulted in many findings, the most prominent of which are as follows: Assault on non-Islamic sacred sites means: doing that which is not permitted, or violating the sanctity of something sacred, such as the rites, places, and persons of non-Muslims. It is prohibited in Sharia to assault a non-Muslim, and likewise to assault their sacred sites by bombing them, killing those within, terrorising their people, or vandalising them. Islamic Sharia has commanded the preservation of places of worship from demolition, ensuring their security and the safety of their adherents. The assailant is punished by imprisonment for a term not less than six months and not exceeding five years, or by a fine under most positive laws. Causes for Exemption from the Penalty for assault on sacred sites are: death, repentance, pardon, and limitation. Finally, the crime of assault on non-Islamic sacred sites affects the economy and sustainable development, as it relates to security, which is the foundation of growth. The researchers recommend the following: Avoidance of conflicts, protection of society from strife, and the dissemination of a culture of engagement with other religions. Decisive formulation of penal provisions in such a manner as to end all controversy raised concerning them by the legal legislator.